Literasi Kesehatan Reproduksi Remaja Dalam Mempersiapkan Generasi Bebas Stunting Pada Siswa Madrasah Aliyah Wihdatul Ulum Parangloe Kabupaten Gowa - Fatmah Afrianty Gobel; Hasta Handayani Idrus; Mansur Sididi (jurnal ABDIMAS Indonesia, 2023)
Adolescent reproductive health is basic knowledge that must be understood by Madrasah Aliyah Wihdatul Ulum students who are growing up as teenagers, in the transition period from childhood. Providing students with knowledge about reproductive health is considered important in order to create awareness about the importance of maintaining reproductive health, so that they have less potential to experience early pregnancy. Pregnancy at teenage increases the risk of giving birth to premature babies and low birth weight (LBW) which is closely related to the risk of stunting. Data from the Parangloe Community Health Center in 2021, the number of stunting cases is still relatively high, namely 43 cases, there are 26 children under the red line (BGM). ) who have the potential for stunting, in 2022 in Bontokasi Village there will be 3 toddlers suffering from stunting. Madrasah Aliyah Wihdatul Ulum students have never received literacy through Communication Information Education (KIE) regarding adolescent reproductive health in relation to stunting, because there is no UKS at the school so it cannot carry out its function in maintaining students' health status and there is no Communication Information Education (KIE) literacy. regarding health in general and regarding reproductive health in particular. Providing adolescent reproductive health literacy education in efforts to prevent stunting using various media, power point slides, standing banners and brochures as well as lecture and discussion methods to increase the knowledge of Madrasah Aliyah Wihdatul Ulum Parangloe students